Bidirectional Regulation of AdpAch in Controlling the Expression of scnRI and scnRII in the Natamycin Biosynthesis of Streptomyces chattanoogensis L10 - Yu, Pin; Bu, Qing-Ting; Tang, Yi-Li; Mao, Xu-Ming; Li, Yong-Quan (Frontiers in Microbiology, 2018)
AdpA, an AraC/XylS family protein, had been proved as a key regulator for secondary metabolism and morphological differentiation in Streptomyces griseus. Here, we identify AdpAch, an orthologue of AdpA, as a ‘higher level’ pleiotropic regulator of natamycin biosynthesis with bidirectional regulatory ability in Streptomyces chattanoogensis L10. DNase I footprinting revealed six AdpAch binding sites in the scnRI-scnRII intergenic region. Further analysis using the xylE reporter gene fused to the scnRI-scnRII intergenic region of mutated binding sites demonstrated that the expression of scnRI and scnRII were under the control of AdpAch. AdpAch showed a bi-stable regulatory ability where it firstly binds to the Site C and Site D to activate the transcription of the two pathway-specific genes, scnRI and scnRII, and then binds to other sites where it acts as an inhibitor. When Site A and Site F were mutated in vivo, the production of natamycin was increased by 21% and 25%, respectively. These findings indicated an autoregulatory mechanism where AdpAch serves as a master switch with bidirectional regulation for natamycin biosynthesis.